On generalized parallelisms - Kolář, I. (Archives of Mechanics, 1998)
M. EPSTEIN AND M. DE LEÓN defined the second order non-holonomic parallelism on a manifold and applied it to a geometric description of generalized Cosserat continua. We explain that the underlying geometric idea is the concept of generalized parallelism on an arbitrary principal fiber bundle. Some properties of generalized parallelisms are characterized in terms of induced connections or from the viewpoint of the theory of generalized G-structures.